Effect of lighting conditions on Zebrafish growth and development - Villamizar, Natalia; Foulkes, Nicholas S. (Zebrafish, 2014)
In the underwater environment, the properties of light (intensity and spectrum) change rapidly with depth and water quality. In this article, we have described how and to what extent lighting conditions can influence the development, growth, and survival of zebrafish. Fertilized eggs and the corresponding larvae were exposed to different visible light wavelengths (violet, blue, green, yellow, red, and white) in a 12-h light-12-h dark (LD) cycle until 30 days posthatching (dph), when the expression of morphometric parameters and growth (igf1a, igf2a)- and stress-related (crh and pomca) genes were examined. Another group of larvae was raised under constant darkness (DD) until 5 or 10 dph, after which they were transferred to a LD of white light. A third group remained under DD to investigate the effects of light deprivation upon zebrafish development. The results revealed that the hatching rate was highest under blue and violet light, while total length at 30 dph was greatest under blue, white, and violet light. Red light led to reduced feeding activity and poor survival (100% mortality). Larvae raised under constant white light (LL) showed a higher proportion of malformations, as did larvae raised under LD violet light. The expression of growth and stress factors was upregulated in the violet (igf1a, igf2a, pomca, and chr) and blue (igf2a) groups, which is consistent with the higher growth recorded and the higher proportion of malformations detected under the violet light. All larvae kept under DD died before 18 dph, but the survival rates improved in larvae transferred to LD at 5 dph and at 10 dph. In summary, these findings revealed that lighting conditions are crucial factors influencing zebrafish larval development and growth.
Gesehen am 22.05.2017